Awareness and Practice Regarding Diabetic Retinopathy Among Diabetic Patients Attending Bir Hospital - Karakheti, Arati; Chhetri, Sundip Dware; Kunwar, Meena; Bhandari, Ipsa (Annapurna Journal of Health Sciences, 2026)
Introduction: Diabetic Retinopathy is one of the major causes of Irreversible blindness. Until too late for treatment patient does not develop any symptoms for Diabetic retinopathy. Timely screening, diagnosis and treatment are must to prevent the burden of eye morbidity due to diabetic retinopathy. Methods: This was a Hospital-Based descriptive quantitative cross-sectional study. It was conducted among 113 study participants from December 15,2024 to June 15,2025. This study followed non-random purposive sampling. Patient with a prior history of intervention for diabetic retinopathy were excluded from this study. IRC approval and well-informed written consent was obtained before data collection. All the collected data were entered in MS- excel sheet. Data collected were later exported to SPSS for analysis. Results: A total of 113 patients were included for this study. The mean age of was 56.1 ± 4.7 years. The median duration since diabetes diagnosis of was 6 years. In the study, 74.3% of participants were aware that diabetes could affect vision and that regular eye exams were necessary. Diabetic retinopathy was found in 36.3 % of participants. Conclusion: To increase the awareness about diabetic retinopathy in diabetic patient is must so as to decrease the burden of irreversible blindness due to diabetes. There is need to develop an awareness program on diabetic retinopathy among diabetic patients.